(untitled) (Revista LIDER, 2021)
Immersed in a world in which the universals becomes more particular and vice versa, we have reached a moment in which the universal is precisely the diverse. The local and the global join in different ways, creating a flow of phenomena that makes you take it from different perspectives. That is why, this essay pretends to make closer by crossing borders of two disciplines (anthropology and philosophy) that have a common objective: the everyday worlds. On one hand, the empiric fact of a particular case; the Mixes of Oaxaca, and on the other side the philosophical vision; emerging from the proposal of Humberto Giannini who analyzes daily life in a topographic way in which social life as the main point of “the moral experience”. On this same plane the separation and complementarity public and private life are generated the subject of this paper. The challenge besides in the fact that there is no clear difference between these domains due to the fact that the group subsumes the individual with all that implies in an indigenous society. At the same time this reflects a struggle for the dominance of some values over others in their way for the collective identity of this daily life in permanent conflict. For all of these speech plays a fundamental roll, because it marks the frontier between two different conceptions of the world, in other aspects, in conflicts an their arrangements by means of moral and juridical norms that come from the “moral experience” of collectivity.